FEATURES OF THE FUNCTIONING OF THE SYSTEM OF ENSURING ECONOMIC SECURITY OF ENGINEERING ENTERPRISES: THEORETICAL BASIS AND PRACTICAL PRINCIPLES - MUZHYLIVSKYI, Nazarii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article substantiates the theoretical and practical foundations of building an effective system for ensuring the economic security of machine-building enterprises. It analyzes the essential and categorical framework of economic security, defining its goals, objects, and key functions within the industrial complex. The research emphasizes that in modern conditions of uncertainty, competition, and technological transformation, the economic security of engineering enterprises becomes a decisive factor of national stability and industrial resilience. The paper identifies the main internal and external threats affecting the sustainable development of enterprises and proposes a typological model of the economic security system as a tool for diagnosing risks and improving management efficiency. The proposed methodological approach involves several stages: assessment of operational and market parameters, identification of threats and vulnerabilities, evaluation of existing protective measures, and the formation of an adaptive model aimed at strengthening the enterprise’s strategic potential.Special attention is paid to the strategic and tactical aspects of managing the economic security system, including planning, monitoring, and information protection mechanisms. The research reveals that economic security management should combine preventive, analytical, and regulatory measures to ensure the integrity of financial, material, informational, and human resources. The implementation of coordinated actions at both enterprise and state levels is considered a prerequisite for enhancing competitiveness and mitigating the consequences of crises. The article also outlines practical guidelines for improving the economic security framework, such as the development of legal and organizational instruments, use of innovative technologies, diversification of financial and logistical flows, and adaptation of international standards.The findings contribute to the formation of a comprehensive scientific basis for the modernization of industrial policy and the development of effective mechanisms for protecting the economic interests of machine-building enterprises in Ukraine’s national security system.
Keywords: economic security system; machine-building complex; machine-building enterprises; ensuring economic security; economic security indicators; economic security model